2002
DOI: 10.1038/sj.onc.1205698
|View full text |Cite
|
Sign up to set email alerts
|

Localization of deletion to a 300 Kb interval of chromosome 11q13 in cervical cancer

Abstract: Previous molecular genetic studies on HeLa cell (a cervical cancer cell line) derived non-tumorigenic and tumorigenic hybrids have localized a tumor suppressor gene to the long arm of chromosome 11. Analysis of cervical cancer cell lines using chromosome 11 specific probes showed deletion and translocation of 11q13 sequences in five out of eight cell lines. Fluorescence in situ hybridization (FISH), using 11q13 specific probes, has shown interstitial deletion of 11q13 sequences in the HeLa cells. In order to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 44 publications
(56 reference statements)
1
34
0
Order By: Relevance
“…Furthermore, evidence from breast cancer cell lines suggests that CST6 promoter hypermethylation leading to gene silencing may represent one major mechanism for loss of cystatin M in breast cancer. CST6 is located in the chromosomal region 11q13, which is subject to amplification or loss of heterozygosity in several cancers (Cromer et al, 2004;Keppler, 2006;Srivatsan et al, 2002). Previously, we reported that the majority of CST6-negative breast cancer cell lines were originally established from metastatic lesions (pleural effusions) rather than primary breast tumors and that CST6-positive breast cancer cell line (BT-20) was derived from a primary breast carcinoma (Rivenbark et al, 2006a).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, evidence from breast cancer cell lines suggests that CST6 promoter hypermethylation leading to gene silencing may represent one major mechanism for loss of cystatin M in breast cancer. CST6 is located in the chromosomal region 11q13, which is subject to amplification or loss of heterozygosity in several cancers (Cromer et al, 2004;Keppler, 2006;Srivatsan et al, 2002). Previously, we reported that the majority of CST6-negative breast cancer cell lines were originally established from metastatic lesions (pleural effusions) rather than primary breast tumors and that CST6-positive breast cancer cell line (BT-20) was derived from a primary breast carcinoma (Rivenbark et al, 2006a).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the most essential factor implicated in the development of CA-CX is infection with HPV (Zur Hausen 1996). However, the discrepancy between high rates of HPV infection and low rates of cervical cancer development suggests that additional genetic alterations must also have a role in its development (Srivatsan et al 2002). Delineation of these genetic changes is crucial in understanding the molecular basis of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Cystatin M has been assigned to chromosome region 11q13, which is the site of loss of heterozygosity (LOH) in several cancer types and is believed to harbour tumour suppressor genes (Stenman et al, 1997;Srivatsan et al, 2002). Cystatin M regulates the activity of cathepsin B and cathepsin L, which are the two most important cysteine proteases implicated in tumour cell invasion and metastasis (Lah and Kos, 1998;Frosch et al, 1999).…”
Section: Introductionmentioning
confidence: 99%